Reading Skills Learning in the "Arabic-Online.net" Application by Saudi Electronic University Based on the Common European Framework of Reference for Languages (CEFR) - Mahmudah, Umi; Musthofa, Tulus (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research focuses on analyzing learning qira’ah (reading) skills in the Arabic-Online.net program within the learning assessment evaluation framework, especially the Common European Framework of Reference for Languages (CEFR) as one of the international standards in foreign language learning. This research is qualitative research, and the primary data in this research is reading text in qira'ah material from all 16 levels in Arabic-Online.net. In the analysis, the researchers focused on the reading texts provided at each level in the program through the CEFR framework. Data analysis in this research used data reduction, data presentation, and drawing conclusions based on Miles and Huberman’s method. The research findings indicate that the reading skills instruction in the "Arabic-Online.net" application offers a diverse range of instructional materials. These materials are designed to help participants comprehensively master reading skills. The content, vocabulary, and exercises within this program align with the CEFR standards. This is demonstrated not only in the selection of themes with higher levels of difficulty but also through the inclusion of more complex questions and exercises. The chosen themes are systematically organized, starting from topics closely related to the participants' experiences and progressing to subjects further removed from daily life, such as transportation, administration, and legal issues. These diverse themes not only require a strong language proficiency with a command of vocabulary related to the themes but also demand critical and exploratory thinking from learners to grasp the discourse and main points of the reading materials.